2019
DOI: 10.1051/0004-6361/201834796
|View full text |Cite
|
Sign up to set email alerts
|

Activity time series of old stars from late F to early K

Abstract: Context. Solar simulations and observations show that the detection of long-period Earth-like planets is expected to be very difficult with radial velocity techniques in the solar case because of activity. The inhibition of the convective blueshift in active regions (which is then dominating the signal) is expected to decrease toward lower mass stars, which would provide more suitable conditions. Aims. In this paper we build synthetic time series to be able to precisely estimate the effects of activity on exop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 99 publications
(171 reference statements)
0
19
0
Order By: Relevance
“…The main advantages conferred by this model are a better statistical significance as several samples can be generated, better noise effect estimation as Ca II time-series are noise-free, and eventually the possibility to look at better temporal sampling. These simulations take the impact of inclination into account, in particular in the construction of the chromospheric emission time-series: Meunier et al (2019b) showed that inclination has an impact on the average level (also found later by Sowmya et al 2021), and also impacts the amplitude of the LT variability. These effects are therefore included in our reconstructions.…”
Section: Appendix B: Correction Of Hα Dependence On B-vmentioning
confidence: 81%
See 1 more Smart Citation
“…The main advantages conferred by this model are a better statistical significance as several samples can be generated, better noise effect estimation as Ca II time-series are noise-free, and eventually the possibility to look at better temporal sampling. These simulations take the impact of inclination into account, in particular in the construction of the chromospheric emission time-series: Meunier et al (2019b) showed that inclination has an impact on the average level (also found later by Sowmya et al 2021), and also impacts the amplitude of the LT variability. These effects are therefore included in our reconstructions.…”
Section: Appendix B: Correction Of Hα Dependence On B-vmentioning
confidence: 81%
“…We first constituted a sample of synthetic time-series similar to the observed ones from the simulations performed in Meunier et al (2019b). Those simulations of complex activity patterns are designed to reproduce a realistic behaviour of F-G-K old main sequence stars, more specifically in the F6-K4 range.…”
Section: Appendix B: Correction Of Hα Dependence On B-vmentioning
confidence: 99%
“…Similarly, Keplerian orbits can be added to the simulated RVs to study the effect of 'red noise' on the planet mass measurements (Gilbertson et al 2020;Meunier & Lagrange 2020). Meunier et al (2019) (2011,2016). Our methods differ from the above work in that we directly use the photometric calibrated granulation and oscillation amplitudes and explicitly show the scaling relations.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Rotational modulation can appear as a dominant frequency peak at the rotation period, as well as several lower-amplitude peaks at orbital harmonic frequencies. As the amplitude of magnetic activity in the form of rotationally modulated variability is more difficult to model, we do not consider these effects here (see However, Meunier et al 2019).…”
Section: Stellar Granulation and Oscillations In The Fourier Spacementioning
confidence: 99%
“…Recently, Morris et al (2018) developed a simple model to show that the precision of Gaia astrometry is insufficient to detect starspot-induced jitter from stars with near-solar activity levels, though it is sufficient to detect jitter of nearby active stars. Meunier et al (2019) proposed a model to simulate astrometric time series for solar-type stars. Using these simulated time series, Meunier et al (2020) quantified the effect of stellar activity on astrometric measurements, and its impact on the search for Earth-mass planets in the habitable zones of old main-sequence solar-type stars.…”
Section: Introductionmentioning
confidence: 99%